Comparison of laparoscopy and laparotomy for the pelvic lymphadenectomy in endometrial cancer at the First Department of Obstetrics and Gynaecology of the Medical Centre of Postgraduate Education in Warsaw: own preliminary experience - Pawłowicz, Paweł; Grzebyk, Katarzyna; Stetkiewicz, Tomasz; Rawski, Wojciech; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2011)
Endometrial carcinoma is one of the most common neoplasms in gynaecological oncology. The 5-year overall survival rate depends on the FIGO stage. For patients with stage I endometrial cancer it is estimated as 80%. Traditionally, the main treatment of endometrial cancer consists of total abdominal hysterectomy with bilateral salpingo-oophorectomy and, in some histological or clinical stages, with additional pelvic lymphadenectomy. A laparotomy has so far been the main surgical approach for women with endometrial cancer. However, the last decades have brought up many reports stating that the survival rate in such cases is similar after laparoscopy and laparotomy. Some researchers claim that laparoscopy is as effective as laparotomy and it might be much more precise than laparotomy thanks to its special optic system. For these reasons, it may become the method of choice in the treatment of stage I endometrial cancer in a short period of time. The preliminary results based on data collected during surgical procedures performed at the First Department of Obstetrics and Gynaecology of the Medical Centre of Postgraduate Education in Warsaw confirm these studies.